Complementary Therapies To Improve The Quality of Life of Premenopause Women - Umi Nur Alifah; Noviyati Rahardjo Putri; Angesti Nugraheni (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2023)
Premenopause is a transitional period experienced by women when they are about to enter menopause. At this stage, a woman will experience a decrease in the hormone estrogen, giving rise to premenopausal syndrome. Common symptoms of premenopausal women due to changes in body systems manifest in complaints in the form of hair loss easily, irritability or sensitivity, insomnia, frequent sweating, and decreased sex drive. These changes and symptoms occur around 2-3 years before menopause. The prevalence of depression and anxiety in women will increase when entering the premenopausal and postmenopausal phases. A study in China described depressive symptoms experienced by women increasing from 14.5% (premenopausal) to 19.6% in the postmenopausal period. The prevalence of anxiety symptoms increases from 3.1% (premenopausal) to 7.4% in the postmenopausal period. This type of research is a literature review. Data is accessed from various existing database sources such as; Google Scholar, PubMed, Science Direct, Sage Pud, ProQuest. Literature reviewed in the range of 2013 to 2023. The main topic search keywords are; complementary, premenopausal, anxiety, quality of life, woman, psychoeducation. The results of this study concluded that providing complementary therapy for premenopausal women has an effective effect on improving quality of life and reducing anxiety in premenopausal women. According to the researchers' analysis, complementary therapy can reduce vasomotor symptoms, reduce stress and depression in women.Â Â